Submarine Capability Assessment Model Using Analytical Hierarchy Process (AHP) and System Dynamics - Prasetyo, A.B.; W, Budisantoso; Nurkarya, Yoyok; Susilo, A.K. (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Regional dynamics marked by the increase in submarine operations by several countries need to be balanced with increasing Indonesia's capabilities in underwater warfare and contributing to increasing the deterrence of the country's defense system at sea. Therefore, the aim of this research is to consider the competitive dimensions of the development of submarine capabilities on the deterrence effect of a country and assess the extent of the discussion in the literature review. This research is a statement that there is no instrument for assessing the capability and sustainability of submarines in an effort to increase the deterrence effect in the ALKI II area which is linked to current dynamic developments so that this research is expected to contribute to obtaining an instrument for assessing submarine capability and the deterrence effect of submarines. in the ALKI II area.